Rheology of environmental friendly hydraulic fluid: effect of aging period, temperature and shear - Wan Nik, W. B.; Ani, F. N.; Masjuki, H. H. (2006)
Limitations of petroleum oil in the aspect of non-renewable, not environmental friendly and its non-sustainability in the future have prompted a search for more stable and environmentally friendly alternatives. Bio-oils are potential to be used as industrial fluids. Currently rheological and tribological aspects of bio-oil are being investigated. Rheological properties of bio-oils used as hydraulic fluid were determined at different aging periods, temperatures and shear rates using a concentric cylinder rotational viscometer. Apparent viscosity versus shear rate was successfully fitted to the generalized Ostwald de-Waele, modified power law, Cross, Carreau and Herschel-Bulkley rheological models. The oils were found to exhibit non-Newtonian, shear thinning behavior at all aging periods and temperatures. The flow behavior index, n, varied in the range of 0.6 to 0.9. The consistency index, K, was in the range of 0.0102 to 0.0485 Pa.sn. Both parameters were significantly affected by temperatures and aging periods.